Wearable Sensor-Based Hand Gesture and Daily Activity Recognition for Robot-Assisted Living - Zhu, Chun; Sheng, Weihua (IEEE transactions on systems, man and cybernetics. Part A, Systems and humans, 2011)
In this paper, we address natural human-robot interaction (HRI) in a smart assisted living (SAIL) system for the elderly and the disabled. Two common HRI problems are studied: hand gesture recognition and daily activity recognition. For hand gesture recognition, we implemented a neural network for gesture spotting and a hierarchical hidden Markov model for context-based recognition. For daily activity recognition, a multisensor fusion scheme is developed to process motion data collected from the foot and the waist of a human subject. Experiments using a prototype wearable sensor system show the effectiveness and accuracy of our algorithms.